Morphometric, Meristic, and Growth Patterns of Mystus nigriceps Valenciannes from the Tarai River, Kampar Regency, Riau Province - Purba, Windu Sani Oksispi; Efizon, Deni; Efawani, Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractMystus nigriceps is freshwater fish that inhabit the Tarai River. A research aims to understand the morphometrical, meristical characteristics and growth pattern of this fish had been conducted from January to March 2019. Sampling were conducted in the Tarai River, using cast net , scoop net and bamboo trap, six times, once/ two week. Result shown that there were 102 fishes (70.93-181.21 mm TL and 4.12-35.7 gr BW) were captured from the river. There were 32 morphological characteristics measured and 6 meristical characteristics counted. There were 4 morphometrical characteristics differences between male and female. In female fish, the distance between mouth to the eye, body width and the distance between dorsal fin to the adipose fin longer than those of the male, but male has longer base of caudal fin. The meristical characteristic of the fish were as follow: D.I.6-8, P.II.10-22, V.8-12, A.7-9, C.16-23. The length-weight relationship shown that the growth of male and female was similar, it was negative allometric with b= 2.339 for male and b= 2.163 for female fish. Keywords: Catfish, adipose fin, negative allometric, fin ray